2008
DOI: 10.1370/afm.859
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Cardiovascular Risk and 15-Year Cardiovascular Mortality

Abstract: PURPOSE Many individuals perceive their cardiovascular disease (CVD) risk to be lower than established clinical tools would estimate, yet little is known about the long-term consequences of holding such optimistic beliefs. We evaluated whether lower self-ratings of CVD risk are associated with lower rates of CVD death after addressing potential confounding by an extensive set of social and biologic CVD risk factors. METHODSWe conducted a 15-year mortality surveillance study of adults aged 35 to 75 years from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…Moreover, in line with findings showing that optimistic beliefs are grounded in reality (Gramling et al, 2008), we found that comparative optimism increased relative to healthier actual food intake and to lower BMI. However, people still rated their own eating behavior to be healthier than their peers' eating when actual healthy eating was unfavorable and BMI was high.…”
Section: Optimistic Perceptions: Grounded In Realitysupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, in line with findings showing that optimistic beliefs are grounded in reality (Gramling et al, 2008), we found that comparative optimism increased relative to healthier actual food intake and to lower BMI. However, people still rated their own eating behavior to be healthier than their peers' eating when actual healthy eating was unfavorable and BMI was high.…”
Section: Optimistic Perceptions: Grounded In Realitysupporting
confidence: 91%
“…First, with increasing actual healthy eating, people might increasingly perceive their eating as healthier than their peers' eating. In this case, people who actually eat healthily would have a greater optimistic view, grounded in reality (de Ridder, Fournier, & Bensing, 2004;Gramling et al, 2008;. Second, people might hold a constant optimistic view of their own compared to their peers' healthy eating regardless of actual healthy eating.…”
Section: Perceptions Of and Actual Healthy Eatingmentioning
confidence: 99%
“…One explanation may be that our sample size was too small to detect a difference. However, it is also possible that unmeasured factors such as a patient's level of activation or their perceived level of risk, which may impact a patient's behavioral choices [14], are more important determinants of choice than age, education, or mFRS-derived risk.…”
Section: Decision Keymentioning
confidence: 99%
“…Gramling and colleagues 13 found that men who rated their 5-year risk of having a stroke or heart attack as "low" went on to have lower-than-expected mortality from cardiovascular disease (CVD) in the subsequent 15 years (controlling for Framingham risk score and other CVD risk factors). Does the men's perception of low risk stem from insider knowledge of their own health, or does optimism protect against cardiovascular events?…”
Section: Epidemiology Relevant To Primary Carementioning
confidence: 99%